(untitled) (CONFERENCE ON THE ROLE AND IMPORTANCE OF SCIENCE IN THE MODERN WORLD, 2025)
This article explores the role of Silphium perfoliatum L. in biomass production, its use as a biofuel source, and its importance in maintaining the ecological stability of agroecosystems. Research indicates that this species is a promising energy crop due to its high biomass yield, low maintenance requirements, long lifespan, and ecological adaptability. The paper also discusses its potential for biogas production, soil fertility preservation, and contribution to biodiversity.